(untitled) (Proximus Journal of Sports Science and Physical Education, 2026)
The study aimed to identify functional variables indicative of muscle damage and to determine the contribution percentages of specific functional variables to performance in the 100-meter freestyle event, as well as to examine the relationships among these functional variables concerning the 100-meter freestyle run. The researcher utilized descriptive survey and correlational methodologies to correspond with the characteristics of the problem being examined. The study population consisted of eight individuals from the 100m junior category runners in Misan Governorate for the 2025 sports season. The study sample consisted of six runners, with two excluded due to injury, representing 75% of the research population. The researchers came to a number of important conclusions. After the juniors ran the 100-meter freestyle race, which was very hard on their bodies, their levels of functional variables went up a lot. This indicates that the traits of quick performance and explosive contractions lead to significant acute muscle damage. Moreover, there exist significant correlations between indicators of muscle damage and performance outcomes, suggesting that the increase of these variables following exertion is associated with a reduction in performance levels, thereby confirming the adverse effects of muscle strain on achievement. The main suggestions were to carefully grade the training loads for juniors to avoid muscle damage that could slow down their physical growth and future performance, and to make recovery a priority after effort, since damage levels go up a lot after speed competitions.